Medical waste management in today’s healthcare: issues and progress - O. V. Kiyok; N. V. Polupanova; N. O. Chernyaeva; L. V. Naprimerova; E. Yu. Enina (Кубанский научный медицинский вестник, 2022)
Background. In every region of the Russian Federation, medical waste management importantly relies on both safe and cost-effective decontamination.Objectives. The study aims to highlight the hygienic aspects of medical waste management in healthcare facilities of Krasnodar Krai and county-wide, as well as to prove the cost effectiveness of the physical decentralised decontamination/neutralisation method in a multi-specialty healthcare facility.Methods. A retrospective analysis of medical waste management over Krasnodar Krai and at a multi-specialty hospital has been conducted for period 2016–2018; cost effectiveness was calculated for the decentralised (physical) method of medical waste decontamination. Statistical analyses were performed with Statistica 10.Results. A high proportion of medical waste has been established for both Krasnodar Krai and country-wide. The cost effectiveness of the physical decentralised waste decontamination method has been demonstrated. The estimates with Ochapovsky Regional Clinical Hospital No. 1 Research Institute showed that a per-kilo deactivation cost for class B (epidemiological hazard) waste by a decentralised (physical) method is more effective amounting to average 38.42 ± 4.48 vs. 191.20 ± 20.46 (p < 0.01) for specialised commercial services of medical waste collection, transportation and neutralisation; the use of a reliable validated physical method warrants the staff epidemiological safety.Conclusion. The cost effectiveness of the physical decentralised method of medical waste decontamination/neutralisation has been demonstrated with a multi-specialty hospital. Better legal regulation and inter-department coordination of medical waste management will upgrade the disposal solutions to ensure compliance with epidemiological and environmental safety.